IMPROVING STUDENTS’ EARLY READING ABILITIES THROUGH PAIKEM APPROACH IN SECOND GRADE OF SDN WOWONG - Gamar Abdul Nasir; Ramadhan Jamhar (Universitas Labuhanbatu, 2023)
This Classroom Action Research (CAR) aims to improve students’ learning process and learning outcomes on their reading skills using PAIKEM approach at Second Grade Students of SDN Wowong. The study is done in 2 (two) cycles, through 4 stages, namely: planning, implementing, observing, and reflecting. The research data are obtained through interviews, observations, tests, and documentation. The data are analyzed descriptive qualitatively and quantitatively. The study shows that PAIKEM approach is effective in improving the learning process and outcomes on the students’ reading skills. This can be seen from the students' attitudes during the learning process; students are active, enthusiastic and enjoy the class. Besides, there is an increase on students’ learning outcomes in cycle II; each student with a score above the KKM (Minimum Completeness Criteria) with an average score of 78.09. It is hoped that this study will provide theoretical benefits, namely adding insight into knowledge about how to apply PAIKEM approach. While practically, this study can contribute ideas and information for schools, teachers and students.Keywords: Skills; Early Reading; PAIKEM Approach. AbstrakPendidikan dasar merupakan fondasi awal bagi anak-anak dalam mempersiapkan diri melanjutkan pendidikan pada tingkat selanjutnya. Salah satunya adalah menyiapkan siswa memiliki kemampuan membaca yang mumpuni. Hasil pengamatan di SDN Wowong, Kecamatan Omesuri, Kabupaten Lembata menunjukkan bahwa banyak siswa di kelas-kelas awal bahkan kelas atas belum mampu membaca dengan baik dan lancar. Siswa masih mengeja kata saat membaca dan terbata-bata. Penelitian Tindakan Kelas (PTK) ini bertujuan untuk meningkatkan proses dan hasil pembelajaran keterampilan membaca permulaan menggunakan pendekatan PAIKEM pada siswa kelas II SDN Wowong. Penelitian telah dilalui dalam 2 (dua) siklus pembelajaran dengan tiap siklus memiliki 4 tahapan, yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Data penelitian diperoleh melalui wawancara, pengamatan, tes, dan dokumentasi dengan prosedur analisis data secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa pendekatan PAIKEM efektif memberikan peningkatan proses dan peningkatan hasil pembelajaran membaca permulaan siswa kelas II SDN Wowong. Hal ini terlihat dari adanya peningkatan sikap siswa saat proses pembelajaran; siswa begitu aktif, antusias dan menyenangkan saat proses pembelajaran. Selain itu, adanya peningkatan hasil belajar siswa pada siklus II; masing-masing siswa dengan nilai di atas KKM (Kriteria Ketuntasan Minimal) dengan rata-rata nilai 78.09.Kata Kunci: Keterampilan; Membaca_Permulaan; Pendekatan_PAIKEM